Oil Exploitation, Environmental Issues and Resource Curse in a Post-Colonial Niger Delta Region of Nigeria: The Unending Search for Peace, 1960-2009 - Ibekwe, Juliet Chinenye; Chidiobi, Okechukwu Christian (Advances in Social Sciences Research Journal, 2022)
The issues surrounding the conflict in the Niger Delta region of Nigeria can never be over-flogged. It is no doubt that so much have been written in this regard, with each paper proffering a possible solution or adding to the numerous suggestions and recommendations already on ground. In spite of these however, the quest for peace has remained elusive or unending because the government and her counterpart multinational oil companies seem not to have really made a genuine or sincere efforts in addressing the myriad of teething issues that have generated conflict in the region ever since the discovery and exploitation of oil. There is therefore the need for a lasting peace and permanent solutions to all the areas of conflicts. If not the situation of the region shall continue to attract comments from scholars, relevant authorities, public affairs commentators, social analysts and concerned or interested opinions. It is thus on this note that this paper comes in handy as modest but useful contribution of the authors to the litany of extant literatures on the lingering conflicts in the region. It is worthy of note that the post-colonial Niger Delta region has never known peace ever since the oil exploitation began in commercial quantity in 1950. The Hobbesian state has almost become the order of the day. Despite the fact that over 90% of the country’s revenue (GDP) is being generated by oil exploitation from the region, the greater majority of the people are still languishing in squalor, in addition to large scale unemployment as well as lack of basic life infrastructural facilities. These obvious denials in the midst of abundance resources coupled with environmental related issues of degradations have been fundamental causes of conflict between the people and the government on one hand, and between the people and the oil extracting companies on the other hand. In view of this ugly development, it is therefore apparent that the gift of oil is now more like a curse than the earlier perceived blessings to the people of the Niger Delta. This study thus examined all the series of failed efforts made by Nigerian government to broker a lasting peace in the region starting from 1960 when the Niger Delta Development Board (NDDB) was established through the recommendation of Sir Willinik Commision of 1957, down to the “Amnesty Program” granted by late president Umar Musa Yar’Adua’s administration in 2009 which led to a large number of the militants numbering 26,808 surrendering their arms to the government in return for technical training and monthly payment of stipends. In spite of the temporal reprieve, there was a resurgence of new militants groups in 2016 seven years down the line. Thus, there is yet to be a definite solution to the conflict in the region as there are still clamour for resource control and occasional threats of militancy activities. In view of this, this paper in addition to many other suggestions already on ground in this respect, also made a number of some useful recommendations that if adopted can bring about lasting peace in the Niger-Delta region.